P245 Can clinical, radiological or laboratory parameters differentiate H1N1 associated pneumonia from community acquired pneumonia?. (2nd December 2011) - Hayes, G E; Sheldon, C D; Patel, B D
Abstract : Pneumonia is a recognised complication of H1N1 influenza, and is an important cause of morbidity and mortality. The Department of Health (DoH) identified characteristics that may aid identification of individuals with H1N1 pneumonia (HNP) from those with community acquired pneumonia not associated with H1N1 infection (CAP). These include severe gastrointestinal symptoms, including diarrhoea and vomiting, myalgia, fever >38 ° C, bilateral CXR changes, a low or normal total WCC, tachycardia and a CRP >200. Lymphopaenia is also reported as a marker of H1N1infection. This study compared the clinical, physiological and radiological characteristics of patients with HNP with those of patients with CAP to determine if these characteristics can reliably identify those with HNP. Methods: A retrospective case notes review of all patients admitted with CAP or HNP to our institution between December 2010 and February 2011. Results: 16 patients with HNP and 52 patients with CAP were identified. Relative to patients with CAP, those with HNP were significantly younger (mean age 49 yrs ±22.1 vs 63 yrs ±23.2, p=0.03), were more likely to present in respiratory failure (92.3% vs 62.5%, p=0.05), or with a temperature >38 ° C (62.5% vs 34.6%, p=0.05), and to report vomiting (71.4% vs 23.1%, p=0.02). There was no significant difference in reported myalgia (80.0% vs 85.0%), diarrhoea (93.8% vs 79.2%). There was no significant difference in the prevalence of unilateral multilobar consolidation (HNP 25.0% vs CAP 17.3%) or bilateral consolidation (31.3% vs 21.5%). Laboratory results showed no significant difference in lymphocyte count (HNP 0.84±0.47 vs CAP 0.95±0.53), CRP (234.3±204 vs 209.0±129) or neutrophil count (9.5±4.8 vs 12.5±7.5). Conclusions: The features stated in the DoH guidelines do not reliably allow clinical differentiation between HNP and CAP. The presence of vomiting, younger age and high fever are suggestive, but not diagnostic, of HNP and viral PCR remains the gold standard diagnostic tool.